The Value of Exemplary in the Film Teach Me Islam and Its Relevance to Islamic Religious Education Materials: Nilai Keteladanan pada Film Ajari Aku Islam Serta Relevansinya dengan Materi Pendidikan Agama Islam - Putri, Dinis Tyas Ayu Karisma; Haryanto, Budi (Indonesian Journal of Education Methods Development, 2022)
The objectives achieved in this research are: 1). To find out and describe what exemplary values ​​are contained in the film Ajari Aku Islam, 2). To find out and explain the relevance of exemplary values ​​in the film Ajari Aku Islam to Islamic religious education materials. The type of research used in this study is a qualitative research content analysis with research subjects showing a film with the title Ajari Aku Islam in the form of scenes containing exemplary values ​​and other sources related to the research objectives, while the analytical technique used is Barthes' semiotics model. . Based on the research that has been done, there are several research results, namely exemplary values ​​such as husnudzan, helping, praying on time, tolerance, loving the Qur'an, sincere, istiqamah, patient, brave, and steadfast.